"Ernest Forward and Grandson Ralph Pike" - Rorke Family (1935)
Ralph Pike and Ernest Forward, with dog Tricksee, outside next to a house. Ernest Edward Forward (1859-1944), son of Capt. Mark William Forward and Mary (Bemister) Forward, was born at Carbonear on 29 May 1859. He married Tryphena Butt on 24 June 1885, and had three daughters: Ernestine (Forward) Pike, Hilda Samways (Forward) Pike and Kathleen (Forward) Rorke. Ernest Forward died on 14 April 1944. Ralph Forward Pike (1924-1985) was the youngest son of Ernestine (Forward) Pike and Arthur S. Pike. He married a woman named Elizabeth and they had two sons, Troy and Mark. He was an orthopedic surgeon in Rhode Island, USA. Dr. Pike died in 1985. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.